Urban camp: a trip through our city (Journal of Parents and Teachers, 2014)
We often tend to travel to other cities, to get to know new cultures, to get lost in the streets, etc. But how much do we know about our own city? We know their stories, legends. . . ? The urban camp is an educational option whose objective is that we rediscover the city with new eyes. To this end, they propose activities that are free and open. In addition, it proposes some examples of this, if you want to know them we invite you to continue reading it.
Keywords: urban camp; city; descubrimiento; education